Shen-Yuan-Dan Capsule Attenuates Atherosclerosis and Foam Cell Formation by Enhancing Autophagy and Inhibiting the PI3K/Akt/mTORC1 Signaling Pathway - Zhou, Mingxue; Ren, Pan; Zhang, Ying; Li, Sinai; Li, Mengjie; Li, Ping; Shang, Juju; Liu, Weihong; Liu, Hongxu (Frontiers in Pharmacology, 2019)
Background and Aim: PI3K/Akt/mTORC1 signaling pathway plays a crucial role in autophagy. Autophagy acts as a negative regulator of inflammation. Our previous studies demonstrated that Shen-Yuan-Dan Capsule (SYDC), a Chinese medicine used for treating angina pectoris, has anti-atherosclerotic effects in mice model and exert anti-inflammatory activities. However, its effects on autophagy and PI3K/Akt/ mTORC1 signaling pathway remains unclear. This study aimed to explore the effect of SYDC on autophagy and PI3K/Akt/mTORC1 signaling pathway in ApoE-/- mice model and ox-LDL-induced macrophage-derived foam cell model to delineate the underlying mechanism. Methods: After 6 weeks of high-fat diet, ApoE/ mice were randomly grouped into control, Lipitor, low-SYDC (SYDC-L), middle-SYDC (SYDC-M), and high-SYDC (SYDC-H) groups (n= 10).The mice were intragastricly administered with the respective drug for 6 weeks. Murine RAW264.7 cells were stimulated with oxidized low-density lipoprotein (ox-LDL) (80 μg/ml) for 24 h and then pretreated with SYDC freeze-dried powder for another 24h. The cells treated by SYDC were co-cultured for 24 hours with LY294002, tricirbine and rapamycin to investigate the possible mechanisms of action. Results: SYDC ameliorated blood lipids, reduced atherosclerotic indexes and plaque areas in aortic root of atherosclerotic mice, and inhibited the total cholesterol (TC) levels and ChE/TC ratios in ox-LDL stimulated macrophages. Moreover, SYDC up-regulated the protein expressions of Beclin1 and LC3Ⅱ/Ⅰratios in aortas of the atherosclerotic mice and ox-LDL stimulated macrophages. Moreover, SYDC inhibited the protein expressions of AKT phosphorylation at Ser473, and mTOR phosphorylation at Ser2448 in aortas of the atherosclerotic mice and ox-LDL stimulated macrophages. Furthermore, the inhibitory effect on ChE/TC ratios of SYDC in ox-LDL stimulated macrophages can be abolished by the selective inhibition of the PI3K/Akt/mTORC1 signal pathway. Conclusions: Taken together, these results highlight that SYDC treatment attenuates foam cell formation by promoting autophagy via inhibiting the activation of PI3K/Akt/mTORC1 signaling pathway. It provides new insights into the molecular mechanism of SYDC and its therapeutic potential on the treatment of atherosclerosis.